PENGETAHUAN, SIKAP, DAN PERILAKU WANITA HAMIL TERHADAP KESEHATAN GIGI DAN MULUT SELAMA MASA KEHAMILAN (: KNOWLEDGE, ATTITUDE, AND BEHAVIOR OF PREGNANT WOMAN TOWARD DENTAL AND ORAL HEALTH DURING PREGNANCY - Dewi Diana; Sayuti Hasibuan (Dentika: Dental Journal, 2010)
Oral health is one of the aspects that should be concerned during the pregnancy. During this time, the hormonal changes may create so me changes in different part of body such as oral and dental. For examples, gingivitis, pyogenic granuloma, dental caries and tooth erosion. These conditions can be prevented if enough and timely care of oral and dental parts i s taken. The aim of this stud y was to know woman’s knowledge, attitude, and practice on oral and dental health during pregnancy. This was a cross sectional study among 100 pregnant women who visited Poliklinik Ibu Hamil RSUD Dr. Pirngadi Medan. Data collected by questionnaire. The res ults showed that only 5% of the pregnant women knew that pregnancy had an effect on their teeth and gums and only 3% of the women knew that oral disease could affect on their fetal health and growth. More than half didn’t know that tetracycline could affec t their baby’s teeth. Only 4% of the women received oral health education, and only 8% of the women reported to have visited dentist during pregnancy. Pregnancy experience was the major sources of oral health education and that all women were brushing their teeth daily, while 37% of the women believed that tooth brushing would reduce gum diseases. In addition, respondents never received an advice to see a dentist during pregnancy from obgyne. In conclusion, most of the participants in this study had in adequate oral health knowledge although majority of them were brushing their teeth daily. Likewise, most of the participants had not received oral health education, and only few of them reported to have dental visits. Therefore, researchers and health program p lanners should give increased attention to the oral health needs and behaviors of pregnant women.